2013
DOI: 10.1002/jgrd.50848
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric SF6: Age of air from the Northern Hemisphere midlatitude surface

Abstract: [1] Observations of SF 6 are used to quantify the mean time since air was in ("mean age" from) the Northern Hemisphere (NH) midlatitude surface layer. The mean age is a fundamental property of tropospheric transport that can be used in theoretical studies and used to evaluate transport in comprehensive models. Comparisons of simulated SF 6 and an idealized clock tracer confirm that the time lag between the SF 6 mixing ratio at a given location and the NH midlatitude surface provides an accurate estimate of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
87
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(103 citation statements)
references
References 34 publications
(54 reference statements)
16
87
0
Order By: Relevance
“…The spatial distribution of the tracer age shown in Fig. 1 is similar to the distribution of idealized or realistic long-lived tracers shown in previous studies (e.g., Denning et al, 1999;Holzer and Boer, 2001;Miyazaki et al, 2008;Waugh et al, 2013) and can be related to the general circulation (e.g., Hadley cells and Intertropical Convergence Zone, ITCZ). There is rapid transport from the NH midlatitude surface into the NH extratropical troposphere, through a combination of along-isentropic and convective mixing, and as a consequence there are weak age gradients in the NH extratropics.…”
Section: Climatological Distributionssupporting
confidence: 82%
See 1 more Smart Citation
“…The spatial distribution of the tracer age shown in Fig. 1 is similar to the distribution of idealized or realistic long-lived tracers shown in previous studies (e.g., Denning et al, 1999;Holzer and Boer, 2001;Miyazaki et al, 2008;Waugh et al, 2013) and can be related to the general circulation (e.g., Hadley cells and Intertropical Convergence Zone, ITCZ). There is rapid transport from the NH midlatitude surface into the NH extratropical troposphere, through a combination of along-isentropic and convective mixing, and as a consequence there are weak age gradients in the NH extratropics.…”
Section: Climatological Distributionssupporting
confidence: 82%
“…Alternatively, recent studies have used observed and simulated SF 6 or simulated idealized mean age tracers to estimate the mean transport time from the NH surface to locations throughout the troposphere (Holzer and Boer, 2001;Waugh et al, 2013). This approach provides a more complete description of interhemispheric transport, quantifying not only differences in transport into the tropics versus southern extratropics but also differences in transport between the lower and upper troposphere.…”
Section: Introductionmentioning
confidence: 99%
“…AoA tracers with linearly growing boundary conditions lead to different concentration gradients than tracers with surface emissions and first-order decay, such as E90. In regions with large gradients, such as the planetary boundary layer and the tropopause, differences in the nu- Our multi-model results agree qualitatively with the study of Waugh et al (2013) that focused on SF 6 and a AoA tracer in a single model (GMI-MERRA). They found "older" AoA than the age derived from SF 6 observations.…”
supporting
confidence: 82%
“…In practical model applications focussing on stratospheric age spectra, G(x, t|t 0 ) is calculated as 30 the response of a time-dependent boundary condition δ(t − t 0 ) specified in a forcing volume in the troposphere. More recently, this concept has also been applied to tropospheric studies (Holzer and Hall, 2000;Waugh et al, 2013;Holzer and Waugh, 2015). In this AoA inter-comparison, we will only analyse the mean age of air.…”
mentioning
confidence: 99%
“…The annual growth of FTIR measurements is 0.265 ± 0.013 pptv year −1 from 2004 to 2016, which is slightly weaker than the trend in the SMO in situ measurements (0.285 ± 0.002 pptv year −1 ) for the same time period. Waugh et al (2013) pointed out that the age of nearsurface SF 6 at SMO (14 • S) is about 0.4 years higher than that on Reunion Island (21 • S). In addition, the global surface in situ measurement network (https://www.esrl.noaa.…”
Section: Methodsmentioning
confidence: 96%